Gut microbiota may be involved in Alzheimer’s disease pathology by dysregulating pyrimidine metabolism in APP/PS1 mice - Feng, Min; Hou, Tianshu; Zhou, Mingze; Cen, Qiuyu; Yi, Ting; Bai, Jinfeng; Zeng, Yun; Liu, Qi; Zhang, Chengshun; Zhang, Yingjun (Frontiers in Aging Neuroscience, 2022)
Introduction Alzheimer’s disease (AD) is the most common form of dementia worldwide. The biological mechanisms underlying the pathogenesis of AD aren’t completely clear. Studies have shown that the gut microbiota could be associated with AD pathogenesis; however, the pathways involved still need to be investigated. Aims To explore the possible pathways of the involvement of gut microbiota in AD pathogenesis through metabolites and to identify new AD biomarkers. Methods Seven-month-old APP/PS1 mice were used as AD models. The Morris water maze test was used to examine learning and memory ability. 16S rRNA gene sequencing and widely targeted metabolomics were used to identify the gut microbiota composition and fecal metabolic profile, respectively, followed by a combined analysis of microbiomics and metabolomics. Results Impaired learning abilities were observed in APP/PS1 mice. Statistically significant changes in the gut microbiota were detected, including a reduction in β-diversity, a higher ratio of Firmicutes/Bacteroidota, and multiple differential bacteria. Statistically significant changes in fecal metabolism were also detected, with 40 differential fecal metabolites and perturbations in the pyrimidine metabolism. Approximately 40% of the differential fecal metabolites were markedly associated with the gut microbiota, and the top two bacteria associated with the most differential metabolites were Bacillus firmus and Rikenella. Deoxycytidine, which causes changes in the pyrimidine metabolic pathway, was significantly correlated with Clostridium sp. Culture-27. Conclusions Gut microbiota may be involved in the pathological processes associated with cognitive impairment in AD by dysregulating pyrimidine metabolism. B. firmus, Rikenella, Clostridium sp. Culture-27, and deoxyuridine may be important biological markers for AD. Our findings provide new insights into the host-microbe crosstalk in AD pathology and contribute to the discovery of diagnostic markers and therapeutic targets for AD.